Isolation and Characterization of a Novel Actinomycete Isolated from Marine Sediments and Its Antibacterial Activity against Fish Pathogens - Haimanti Mondal; John Thomas (MDPI AG, 2022)
Marine habitats are especially complex, with a varied diversity of living organisms. Marine organisms, while living in such intense conditions, have developed great physiological and metabolic potential to survive. This has led them to produce several potent metabolites, which their terrestrial counterparts are unable to produce. Over the past few years, marine Actinomycetes have been considered one of the most abundant sources of diverse and novel metabolites. In this work, an attempt was made to isolate Actinomycetes from marine sediments in terms of their ability to produce several novel bioactive compounds. A total of 16 different Actinomycete colonies were obtained from marine sediment samples. Among the 16 Actinomycete isolates, 2 isolates demonstrated in vitro antibacterial activity against Aeromonas hydrophila and Vibrio parahemolyticus. However, among them, only one isolate was found to have potent antibacterial activity, and hence, was taken for further analysis. This isolate was designated as Beijerinickia fluminensis VIT01. The bioactive components obtained were extracted and later subjected to Fourier transform infrared spectroscopy (FTIR) and gas chromatography-mass spectroscopy (GC-MS) analyses for identification. Several novel bioactive compounds were reported from the data obtained and were found to have potent antibacterial activity. Hence, they could be used as an alternative to antibiotics for treating several fish pathogens in the aquaculture industry.